Glycated nisin enhances nisin's cytotoxic effects on breast cancer cells - Ali Mohammadi; Nasrin Kazemipour; Gholam Abbas Ghorbankhani; Solmaz Morovati; Mahdi Hashempour Sadeghian (Scientific Reports, 2024)
Abstract Antimicrobial peptides, such as nisin, are proposed as promising agents for cancer treatment. While glycation has been recognized as an effective method for enhancing various physicochemical properties of nisin, its anticancer effects remain unexplored. Therefore, we aimed to assess the anticancer potential of glycated nisin against MDA-MB-231 cells. The MDA-MB cells were treated with increasing concentrations of nisin and glycated nisin for 24, 48, and 72 h. The IC50 values for nisin were higher than those for glycated nisin. Glycated nisin at concentrations of 20 and 40 µg/mL decreased cell viability more than nisin at the same concentrations. The rate of apoptosis in the group treated with 20 µg/mL of nisin was lower compared to other treatment groups, and no significant difference in apoptosis rates was observed at different time points (p > 0.05). However, in the glycated nisin groups with concentrations of 10, 20, and 40 µg/mL, the level of apoptosis was very high after 24 h (73–81% of cells undergoing apoptosis). Overall, our study suggests that glycated nisin exhibits stronger cytotoxic effects on MDA-MB-231 cells, primarily involving the induction of apoptosis. This indicates its potential utilization as an alternative approach to address the issue of drug resistance in cancer cells.